"Hitting the ground running": preparing groups for outdoor learning using a theoretically-based video. Issue 1 (2nd January 2020) - Cooley, Sam J.; Eves, Frank F.; Cumming, Jennifer; Burns, Victoria E.
ABSTRACT: Our thoughts and feelings towards groupwork and outdoor learning impact our subsequent engagement in, and learning from, such activities. This study explores the impact of a pre-course video when used in preparation for an outdoor groupwork skills course. The video was designed according to the theory of planned behaviour (TPB) to enhance intentions to develop groupwork skills in an international cohort of university students. At the induction session of the 3–5 day residential course ( N = 173), participants were assigned to either video-only, video with goal-setting worksheet, or control conditions. Their thoughts and feelings towards the course were measured pre- and post-induction and their groupwork skills were measured pre- and post-course. In line with the TPB, participants' attitudes and self-efficacy towards the course were significant and meaningful predictors of their learning intention and subsequent behaviour change. These pre-course beliefs towards groupwork and outdoor learning were significantly improved by the video, despite learners already holding favourable beliefs at baseline. However, these high baseline scores meant that improvements in attitudes resulting from the video were small, and not enough to enhance the subsequent learning outcomes. The potential mechanisms of the pre-course video are discussed along with practical implications.